Peningkatan Hasil Belajar Materi Induksi Magnet Melalui Model Pembelajaran Team Assisted Individualization Pada Siswa Kelas XII MIA 3 SMAN 2 Pontianak - Udzaenah, - (Jurnal Pembelajaran Prospektif, 2016)
This research was aimed to increase student’s achievement of XII MIA 3 students of SMA Negeri 2 Pontianak on magnetic induction materials. This research consist of 2 (two) cycles with each meeting takes time 3x45 minutes. Each cycle consisted of planning, implementation, observation, and analysis section.To know class management, teacher and student;s observation sheet was used.The results showed that application of cooperative learning model Team Assisted Individualization can improve student’s achievement in class XII MIA 3 SMA Negeri 2 Pontianak on magnetic induction material. It can be seen from the increase in average grade from 67.9 to 76.32 and the percentage of students who pass the test rosefrom 52.63% in the first cycle becomes 76.32% in the second cycle.